2016
DOI: 10.1016/j.apmr.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Types of Mobilization Techniques in Patients With Primary Adhesive Capsulitis of the Shoulder: A Systematic Review

Abstract: Overall, mobilization techniques have beneficial effects in patients with primary AC of the shoulder. Because of preliminary evidence for many mobilization techniques, the Maitland technique and combined mobilizations seem recommended at the moment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 28 publications
0
42
0
4
Order By: Relevance
“…Although there are no specific recommendations for shoulder dysfunction in the HNC population, recommendations for shoulder dysfunction from the general population may include an intraarticular corticosteroid injection for pain modulation, capsular distension under ultrasound or fluoroscopic guidance, or 3-quadrant ultrasound to deep heat collagen structures. 54,55 For patients who completed HNC treatment relatively recently, sonographic heating of the shoulder should only be done with medical supervision because of the theoretical chance of tumor spread due to increased blood flow brought on by heating. For impairments like myofascial pain, trigger-point injections may be beneficial in reducing focal dystonia and pain.…”
Section: Screening For Spcs Seementioning
confidence: 99%
“…Although there are no specific recommendations for shoulder dysfunction in the HNC population, recommendations for shoulder dysfunction from the general population may include an intraarticular corticosteroid injection for pain modulation, capsular distension under ultrasound or fluoroscopic guidance, or 3-quadrant ultrasound to deep heat collagen structures. 54,55 For patients who completed HNC treatment relatively recently, sonographic heating of the shoulder should only be done with medical supervision because of the theoretical chance of tumor spread due to increased blood flow brought on by heating. For impairments like myofascial pain, trigger-point injections may be beneficial in reducing focal dystonia and pain.…”
Section: Screening For Spcs Seementioning
confidence: 99%
“…One reviewed 12 RCTs involving 810 patients. 41 This SR found that mobilization techniques have beneficial effects in patients with primary AC of the shoulder. It reported that the Maitland technique and spine mobilization, combined with glenohumeral stretching and both angular and translational mobilization, seem to be most beneficial in reducing pain.…”
Section: Manual Therapymentioning
confidence: 93%
“…Three studies 5,6,21 were scored as high quality, and 3 were scored as acceptable quality. [39][40][41] Two of the high-quality studies were conducted by the same research team. 5,6 The first meta-analysis reviewed the evidence of electrotherapy modalities, delivered alone or in combination with other interventions, for the treatment of AC.…”
Section: Adhesive Capsulitismentioning
confidence: 99%
“…Many treatments have been proposed for FS including conservative (i.e. manual therapy) [4], and non-conservative approaches (i.e. arthroscopic capsular release) [5].…”
Section: Introductionmentioning
confidence: 99%